Microsoft Exchange server 2003 deployment and migration : - McCorry, Kieran (Elsevier Digital Press, 2006)
This book covers, in detail, the tools and techniques that messaging system planners and administrators will require in order to establish a functioning interoperability environment between Exchange 2003 and previous versions of Exchange including Exchange 5.5 and Exchange 2000